Early developmental outcomes following newborn encephalopathy - Dixon, G.; Badawi, N.; Kurinczuk, J.; Keogh, J.; Silburn, Sven; Zubrick, Stephen; Stanley, F. (American Academy of Pediatrics, 2002)
Objective. The aim of this study was to ascertain the early developmental status of children who have a history of newborn encephalopathy.Methods. A longitudinal follow-up was conducted of a population-based, case-control study of children born in Western Australia between June 1993 and December 1996. The study included 276 term children (37 weeks' gestation) with moderate or severe newborn encephalopathy and 564 unmatched term control subjects. The Griffiths Mental Development Scales was used to ascertain developmental status and a General Quotient (GQ) score. Outcome measures were the Griffiths developmental subscales, GQ, diagnosis of cerebral palsy, and mortality.Results. Thirty-four patients and 1 control subject died before reaching assessment. Between June 1994 and December 1999, 195 (81%) eligible patients and 445 (79%) eligible control subjects were assessed. Statistically significant differences were found between patients and control subjects for GQ and all developmental subscales. Overall, 39% of patients had a poor outcome as defined by death, cerebral palsy, or a significant degree of developmental delay, compared with 2.7% of control subjects. Furthermore, 62% of those with severe encephalopathy had a poor outcome compared with 25% of those with moderate encephalopathy. Patients with a history of seizures were 3 times more likely to develop cerebral palsy than patients without. Overall, 28 (10.1%) of patients have cerebral palsy.Conclusions. These data provide important prognostic information regarding survival and serious disability and indicate that newborn encephalopathy places children at significant risk of developmental delay by their second year. These findings also suggest that comprehensive clinical and educational assessments are required to enable appropriate educational provisions as these infants approach school entry.